Innovative Student Worksheets in Operations Research for Better Engagement and Outcomes - Puji Subekti; Widya Adhariyanty Rahayu (LPPM Undiksha, 2025)
Instruction in Operations Research courses often faces challenges in the form of low student participation and difficulties in understanding concepts that are both abstract and applied in nature. These challenges negatively affect students’ learning outcomes. This study aims to develop an Innovative Student Worksheet based on Problem-Based Learning (PBSW) for an Operations Research course and to examine its effect on student engagement and learning outcomes. The study employed a quasi-experimental design with pre-test and post-test involving 42 fifth-semester undergraduate students. The developed PBSW incorporates real-world problem-solving scenarios, group discussion guidelines, and data analysis procedures to promote active learning. Data were collected through conceptual understanding tests and observations of student engagement during lectures. The results show an increase in the mean score from 66 to 83, with more evenly distributed scores in the post-test. Paired Sample t-test analysis indicates a statistically significant improvement. These findings confirm that PBSW is effective in enhancing students’ conceptual understanding, critical thinking skills, and problem-solving abilities. The implications of this study recommend the broader implementation of PBSW in courses that require data analysis and problem-based decision making.